Pengaruh Harga Dan Celebrity Endorser Terhadap Keputusan Pembelian Produk Skincare Skintific - Siti Nabillah Suci Amanda; Ayuni Ayuni; Ajat Sudrajat (Jurnal Ilmiah Wahana Pendidikan, 2023)
The purpose of this study was to determine, analyze, and explain the effect of Price and Celebrity Endorser on Purchasing Decisions of Skintific skincare products. This study uses quantitative research where the population of this study is Skintific skincare product users. The data collection method uses a questionnaire with a sample size of 100 respondents. The data analysis method used is multiple linear regression analysis using SPSS 25. The results show that the variables of Price and Celebrity Endorser have a positive and significant effect on Purchase Decision. Keywords: Price, Celebrity Endorser, Purchase Decision, Skintific